Factors related to painful somatic symptoms in patients with depression: The role of gender and anhedonia - A. Pérez-Morenilla; A. Salazar; I. Failde; F. González-Sáiz; J.A. Micó (Psychiatry Research Communications)
Background: Pain is common in Major Depressive Disorder (MDD), but other related factors have received scant attention. The aim was to know the factors related to Painful Somatic Symptoms (PSS) in MDD patients, especially gender and anhedonia. Methods: Cross-sectional study in MDD patients (DSM-5) with positive screening on the Hospital Anxiety and Depression Scale (HADS). Anhedonia (SHAPS), somatic symptoms (SSI-28), and Quality of Life (QoL; SF-36) were evaluated. A multiple linear regression model was used to identify factors related to PSS. Results: In N = 111 patients, PSS were related to gender, rheumatic disease and anxiety, and worsened QoL. Anhedonia was detected in 93 patients (83.8%), with no significant gender differences in PSS. However, compared to men, depressed women with anhedonia had significantly higher scores on the SSI-28 and the non-painful somatic symptom scale (SSI-21). In the group without anhedonia (n = 18), a higher percentage of women had PSS. Conclusions: Some factors, including gender or anhedonia, influence the presence of PSS in MDD patients. In depressed patients with anhedonia, gender differences in the perception of pain were smaller than in patients without anhedonia. This suggests a diminished capacity to perceive pain. This small difference between gender was not evidenced for non-painful somatic symptoms.